Encyclopedia fo food and color additives Vol; II F-O - Burdock , George A. (Boca Raton CRC Press, 1996)
ontains profiles of 2,500 food additives and ingredients. This book provides the answers to technical, legal, and regulatory questions. It contains descriptions of substances listed in the Everything Added to Food in the US (EAFUS) database, including food additive categories and some substances not considered to be 'additives', such as corn oil
Keywords: Food additives -- Encyclopedias; Coloring matter in food -- Encyclopedias; Aliments -- Additifs -- Encyclopédies.